ANALYSIS OF COST STRUCTURE FOR PHARMACOTHERAPY OF PATIENTS WITH STABLE ANGINA (THE CASE OF CARDIOLOGY DEPARTMENT OF TVER REGIONAL CLINICAL HOSPITAL) - M. A. Demidova; N. N. Kirilenko (Столичная издательская компания, 2015)
Aim. To analyze the cost structure for pharmacotherapy of patients with stable angina (SA), in particular, to compare the cost of pharmacotherapy with drugs, both included and not included into the official Standard of care (SC). Material and methods. Medical records of patients with SA (n=100) admitted to the cardiology department of Tver Regional Clinical Hospital in January-July 2010 were studied retrospectivelly. Costs of treatment with drugs specified in SC for patients with SA as well as drugs not included in SC were considered. Costs of pharmacotherapy and cost structure were determined. Pharmacoeconomical methods, especially ABC analysis, were partially used.  Results. Totally 65502.39 ruble was spent for pharmacotherapy of 100 patients with SA. Cost structure was the following: 32679.34 ruble was spent for drugs recommended by SC, 23698.18 ruble - for drugs not included in SC, and 9124.87 ruble - for drugs to treat concomitant diseases which are not taken into account by SC for patients with SA. Conclusion. SA pharmacotherapy counts 50% of the total cost for drugs recommended by SC, 36% - for drugs not included in SC but belonged to pharmacological class presented in SC, and 14% - drugs from pharmacological class not included in SC. In the process of new SC elaboration for SA patients it is necessary to take into account treatment costs of concomitant diseases especially diabetes mellitus which can account up to 9.5% of total treatment cost of SA patients.